Health experience model of personal informatics: The case of a quantified self. (April 2017) - Shin, Dong-Hee; Biocca, Frank
Abstract: The "quantified self" movement and wearable devices with health monitoring and activity tracking functions are experiencing increased popularity, as they allow users to become more aware of their health-related behavior. This paper describes the user experience of the quantified self as examined through multiple methods. First, we surveyed people's motivations and attitudes toward the quantified self. Second, we investigated the psychological effects of the form of health feedback (comparative vs. non-comparative) and presentation mode (text vs. image) on users' health preservation tendencies to identify more effective ways of delivering health information to users. The results of this user model confirm the significant role of utility and hedonicity regarding their underlying link to confirmation, satisfaction, and continuance intention. A between-subjects experiment reveals that health information provided in a comparative and textual format is more effective in encouraging health preservation in participants than the identical information presented in a non-comparative image format. In addition, participants' health-consciousness is found to be a significant determinant of health preservation. The findings show that users' health experience relates both utilitarian and hedonic aspects of motivation. The findings establish a foundation for future wearable technologies through a heuristic quality assessment tool from a user-centered perspective. Highlights: Quantified Self User Study. User motivations and attitudes toward quantified self. Effective ways of delivering health information to users. The effect of the psychological effects of forms of health feedback and presentation modes on user tendencies.